La medicina oltre la cura (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Within bioethical debate the dichotomy “to cure”/ “to care” is often used in order to focus on the complexity of the concept of health and – like in a game of mirrors – of each activity aimed to the protection of health. This dichotomy works well also if applied to the role of medicine. Nobody denies that among medicine’s functions and at the foundations of the ancient and modern medicine there is the care of patient, the mission to look after his needs in a global meaning and not only at a clinical level; however, everybody could pacifically observe that the specific mission of medicine, which distinguishes that from the other health care activities, is its capacity to cure the patient. Nevertheless, nowadays, thanks to the scientific and technological progress and to the evolution of the conception of health itself, the increasing power of medicine in our societies seems pushing it beyond the borders of the cure, not only towards the care, but also out of the scheme of the classic aforesaid dichotomy. This paper, by a constitutional studies’ point of view, deals with this issue by: i) analysing the contribution given by the Italian Constitution (starting from the Constituent Assembly debates) to overcome a limited notion of health protection (in the sense of the cure); ii) looking for (at a legal level) the current tendencies of medicine to go beyond the cure.
Keywords: To care; to cure; medicine; healthcare; future